Hubungan Ekspresi Imunohistokimia Matrix Metalloproteinase-9 dengan Tumor Budding Peritumoral dan Subtipe molekuler pada Invasive Breast Carcinoma of No Special Type - Indriani Saragih, Septina; Delyuzar, Delyuzar; Intan, T. Kemala (Majalah Patologi Indonesia, 2025)
Abstract Background Breast cancer ranks first most often in the world and is a malignant cancer that often occurs in women. Matrix metalloproteinase-9 (MMP-9) has been the focus of attention in several previous studies in the field of breast cancer. MMP-9 plays a role in the degradation of the extracellular matrix. High expression of MMP-9 is associated with tumor aggressiveness, metastatic potential and poor prognosis. The presence of tumor budding and molecular subtypes also indicates tumor aggressiveness, one of which is the potential for metastasis through extracellular matrix degradation. The aim of this study was to analyze the association of MMP-9 mmunohistochemistry expression with peritumoral tumor budding and molecular subtypes in IBC-NST. Methods This study is an analytic study with a cross sectional approach on 41 samples of paraffin block cases of IBC-NST which had been diagnosed histopathologically and then performed with MMP-9 mmunohistochemistry staining. The correlation between the immunohistochemical expression of MMP-9 with peritumoral tumor buds and molecular subtypes in IBC-NST was tested statistically using Somers'd test and Eta test. Results There was a significant relationship between the immunohistochemistry expression of MMP-9 with peritumoral tumor budding and molecular subtypes. Conclusion Reporting the results of MMP-9 expression on IBC-NST can be one of the prognostic criteria that can be applied in routine examinations. However, the relationship with prognosis cannot be concluded from this study because it is not associated with survival rate